Sudden stops, time inconsistency, and the duration of sovereign debt - Hatchondo, Juan Carlos (IMF Working Papers; Working Paper ;, 2013)
We study the sovereign debt duration chosen by the government in the context of a standard model of sovereign default. The government balances off increasing the duration of its debt to mitigate rollover risk and lowering duration to mitigate the debt dilution problem. We present two main results. First, when the government decides the debt duration on a sequential basis, sudden stop risk increases the average duration by 1 year. Second, we illustrate the time inconsistency problem in the choice of sovereign debt duration: governments would like to commit to a duration that is 1.7 years shorter than the one they choose when decisions are made sequentially.